Localized scleroderma in children - Katarzyna A. Wolska-Gawron; Dorota Krasowska (Termedia Publishing House, 2020)
Localized scleroderma is an autoimmune disease affecting the dermis and underlying tissues (subcutaneous tissue, fascia, muscles, bones). The disease mainly occurs in women aged 20-50 years; however, children aged 7-10 years represent about 15% of all cases. Clinical course of juvenile localized scleroderma is classified with regard to its activity/severity as well as extent and depth of lesions. Some clinical subtypes of juvenile localized scleroderma, characterized by severe course, need to be monitored regularly to prevent irreversible sequelae. The treatment of juvenile localized scleroderma depends on the clinical subtype of the disease, its severity/activity and extent of skin lesions.